Pengaruh Sudut Camber Roda Depan pada Kemampuan Belok Mobil Model 4 dan 2 Roda Penggerak (4WD dan RWD) - Joni Dewanto; Dicky Efendi (Institute of Research and Community Outreach, Petra Christian University, 2013)
Some experts had conducted research on vehicles dynamics and stability through the various modeling and simulation. This paper proposes an experimental base research about influence of front wheel camber angle on cornering ability of 4 wheel vehicle. The experiment performed on four and two rear wheel drive of a remote control vehicle model car with variables front wheel camber angle and speed of vehicle. The result showed that negative front wheel camber angle impact could reduce the turning ability of vehicle. Four wheel drive car has better turning ability than two rear wheel drive car. The best turning ability of car accomplished if the front wheel camber angle is set at 00.